Young Abusers - The Star, Sharmila Nair (2008)
Mass Communication student Katherine does not think that she is a drug addict. Even though she has smoked marijuana for eight years, the bubbly college student believes she is not dependent on drugs. It has been two months since Katherine last smoked a joint, and she is confident she can hold off till the next semester break in July.